NAVIGATING SME INNOVATION THROUGH FINANCE: A SYSTEMATIC REVIEW OF CAPITAL CHANNELS - Salsabila , In'am Fairuz (Generate Digital Publishing, 2025)
Objective: This study systematically synthesizes the dynamics of SME innovation financing channels, highlighting how financing characteristics, internal capacity, and institutional support influence access to and effectiveness of financing in various countries. Research Design & Methods: This study uses a Systematic Literature Review (SLR) approach on 65 articles indexed in Scopus and Web of Science published between 2013 and 2024. Analysis was conducted through thematic coding to group findings into internal, external, and interaction patterns of financing channels. Inclusion and exclusion criteria were determined based on the PRISMA method to ensure transparency and validity of the selection process. Findings: The study results indicate that the effectiveness of SME innovation financing is highly determined by a combination of internal financial literacy, digital readiness, and the quality of the regulatory ecosystem. There are patterns of complementarity and substitution among financing channels that depend on the growth phase of SMEs. Developed countries have shown success through blended finance schemes and integrated incentive policies, while developing countries face challenges in the form of policy fragmentation and data access gaps. Implications & Recommendations: These findings have important implications for policymakers, namely the need to build an evidence-based regulatory framework that encourages cross-agency collaboration and support for alternative financing channels. For SMEs, improving digital and managerial literacy is key to maximizing opportunities for access to innovation financing. Strategic recommendations include strengthening the role of incubators, leveraging fintech, and integrating financing information systems. Contribution & Value Added: This research contributes conceptually by developing an integrative framework between financing channels, internal capabilities, and institutional support in the context of SME innovation. The study also expands cross-country understanding and offers a more adaptive policy basis for developing innovative financing systems in the digital age.